Edukasi Literasi : Meningkatkan Minat Baca Anak-Anak di SDN 032 Tanjung Batu Tarakan sebagi Upaya Pengabdian Masyarakat di Wilayah Pesisir - Nurul Hidayat; Miko Aji Saputra; Nisa’ul Alamin; Fitri Nur Ilham; Juliana Rosita; Destri Emiliana (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
Literacy in the sense of the ability to read and write initially has a very important role, literacy in the early grades is the basis for determining success in student learning activities, but there are still students in elementary schools who are not able to read and write (literacy) well. So researchers are interested in conducting research with the title "Student Abilities and factors that influence literacy". This service activity was carried out at SDN 032 Tanjung Batu Tarakan on September 21 2024 at 08:00-11:30 WITA. The formulation of the problem in this research is "What factors influence the literacy of children at SD Negeri 032 Tanjung Batu Tarakan?". This research aims to determine various factors that influence children's literacy taught at school. This research uses a qualitative approach with descriptive research type. The subjects in this research were students whose literacy was still lacking at SD Negeri 032 Tanjung Batu Tarakan, totaling 68 students consisting of 44 boys and 24 girls. Data collection was carried out using tests and interviews. The research results obtained in this study are that there are several factors that influence children's literacy, including the educational background of parents, the tutoring they receive, the family (level of family concern) and genes (heredity).